1984
DOI: 10.3758/bf03198427
|View full text |Cite
|
Sign up to set email alerts
|

The similarity and diversity of semantic relations

Abstract: There is a rich variety of semantic relations in natural languages. Subjects' perceptions of similarities among relations were studied for a wider variety of relations than had been used in previous studies. Forty subjects sorted 31 cards bearing five example pairs of each of 31 semantic relations. Subjects were able both to distinguish the relations and to perceive their similarities. A hierarchical clustering analysis of the sorting data indicated that the subjects perceived five families of semantic relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
81
0
3

Year Published

1985
1985
2006
2006

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 31 publications
4
81
0
3
Order By: Relevance
“…Adults can make comparisons among semantic cases in a manner similar to the way they compare ordinary taxonomic categories (Chaffin & Herrmann, 1984;Shafto, 1973). The language of young children reflects their growing awareness of different semantic cases (Bowerman, 1973).…”
mentioning
confidence: 99%
“…Adults can make comparisons among semantic cases in a manner similar to the way they compare ordinary taxonomic categories (Chaffin & Herrmann, 1984;Shafto, 1973). The language of young children reflects their growing awareness of different semantic cases (Bowerman, 1973).…”
mentioning
confidence: 99%
“…In psychology, the focus has been mostly on classical relations; however, there have been recent calls to broaden the focus and include non-classical relations as well (McRae and Boisvert, 1998;Hodgson, 1991). Some researchers have always included some non-classical relations, such as Evens et al (1983), Chaffin and Herrmann (1984), and researchers in Library and Information Science. However, as stated earlier, the research on lexical semantic relations has been done out of the context of text, and then assumed to be relevant within it, and in lexical cohesion research, the analysis of lexical semantic relations was done by experienced linguists with particular points of view.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The purpose of the present research was to ascertain whether perceptions of relation similarity originate in a comparison of relational elements similar to those used in linguistics to define relations (Leech, 1974;Lyons, 1968Lyons, , 1977. If it could be shown that perceptions of relation similarity vary with the overlap in relation definitions, then the theory that the comprehension of relations involves processing definitional elements of relations would gain further support (Chaffin & Herrmann, 1984a, 1984bJohnson-Laird, Herrmann, & Chaffin, 1984; see also Klix, Hoffman, & van der Meer, 1983).…”
mentioning
confidence: 99%
“…A recent study (Chaffin & Herrmann, 1984b) showed that relation similarity varies systematically across relations. The study required subjects to sort word pairs that represented 31 relations into groups of similar relations.…”
mentioning
confidence: 99%
See 1 more Smart Citation